The bulldozer and the big tent : - Gitlin, Todd (John Wiley & Sons, 2007)
A social critic presents an analysis of the American political system, addressing such issues as why baby boomers have produced few impressive politicians, why Barack Obama has become popular so quickly, and who has won the culture war.